Composite dressing for long-acting promotion of skin wound healing and preparation method and application thereof

By using a composite dressing composed of carboxymethyl chitosan, silk nanofiber hydrogel and forskolin, the problems of low drug delivery efficiency and single function of existing wound dressings are solved, and the effect of promoting skin wound healing is achieved in a long-term effect.

CN119701077APending Publication Date: 2025-03-28GENERAL HOSPITAL OF PLA
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411956088.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-28
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

Existing wound dressings lack bioactivity, low drug delivery efficiency, single function, and poor biocompatibility and biodegradability, affecting wound healing.

Method used

A composite dressing consists of carboxymethyl chitosan, silk nanofiber hydrogel and forskolin, which promotes angiogenesis through controlled release of forskolin, thereby accelerating wound healing.

Benefits of technology

This composite dressing not only provides physical protection and a humid environment, but also promotes skin wound healing through slow release of forskolin, improves drug delivery efficiency, expands the functionality of the dressing, and reduces scar formation.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119701077A_ABST
    Figure CN119701077A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of wound surface dressings, and provides a composite dressing capable of promoting skin wound surface healing for a long time and a preparation method and application thereof, the composite dressing capable of promoting skin wound surface healing for a long time comprises the following raw materials: carboxymethyl chitosan, silk nanofiber hydrogel and a Maohou element. According to the technical scheme, the problems of low drug delivery efficiency and single function of wound dressing in related technologies are solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of wound dressings, and in particular to a composite dressing for promoting skin wound healing in a long-term manner, and a preparation method and application thereof. Background Art

[0002] In modern medicine, skin repair after injury has always been an important and challenging topic. As the largest organ in the human body, the skin not only protects the body from external physical, chemical, and biological factors, but also has multiple functions such as regulating body temperature and sensing external stimuli. Therefore, wound healing requires not only rapid closure of the wound, but also minimizing scar formation and maintaining the normal function of the skin.

[0003] Wound healing is a complex biological process, including four stages: hemostasis, inflammation, proliferation and remodeling. Ideal wound healing should promote the smooth progress of these four stages while reducing the formation of scar tissue. Currently, although the existing wound dressings on the market can provide certain protection and moist environment for the wound, they often have the following problems and shortcomings: 1. Lack of biological activity: Many traditional dressings only provide a physical barrier and lack biologically active components that promote cell proliferation, migration, and angiogenesis.

[0004] 2. Low drug delivery efficiency: Although some dressings attempt to integrate drug delivery, due to the lack of an effective controlled release system, the drug delivery efficiency and cycle often cannot meet clinical needs.

[0005] 3. Biocompatibility and biodegradability issues: Some dressings have poor biocompatibility and biodegradability, which may cause allergic reactions in patients or accumulate in the body, thereby affecting wound healing.

[0006] 4. Single function: Most dressings focus on protecting or moisturizing the wound surface and lack comprehensive functions to promote wound healing, such as anti-infection and scar reduction.

[0007] Therefore, it is necessary to provide a composite dressing that can promote skin wound healing in a long term, so as to improve the drug delivery efficiency and expand the functionality of the wound dressing. Summary of the invention

[0008] The present invention provides a composite dressing for promoting skin wound healing in a long-term manner, and a preparation method and application thereof, which solve the problems of low drug delivery efficiency and single function of wound dressings in the related art.

[0009] The technical solution of the present invention is as follows: The invention provides a composite dressing for promoting skin wound healing in a long-term manner. The raw materials of the composite auxiliary material include carboxymethyl chitosan, silk nanofiber hydrogel and forskolin.

[0010] As a further technical solution, the concentration of forskolin in the composite dressing is 5-15 μM. As a further technical solution, the concentration of forskolin in the composite dressing is 10 μM.

[0011] The present invention finds that when the concentration of forskolin in the composite dressing is 10 μM, the promoting effect of the composite dressing on cell proliferation can be further improved to ensure cell vitality.

[0012] The present invention also proposes a method for preparing a composite dressing for promoting skin wound healing in a long-term manner, comprising the following steps: S1, adding degummed silk into silk dissolving solution and mixing evenly to obtain silk nanofiber hydrogel; S2, mixing the carboxymethyl chitosan aqueous solution and the silk nanofiber hydrogel evenly to obtain a mixed gel; S3. Evenly mix the forskolin and the mixed gel to prepare a composite dressing.

[0013] As a further technical solution, the degummed silk is obtained by degumming silk with a sodium bicarbonate solution.

[0014] As a further technical solution, the silk is mulberry silk.

[0015] As a further technical solution, the method for preparing the degummed silk is: using 0.05wt%~0.1wt% sodium bicarbonate aqueous solution to boil the silk to obtain the degummed silk.

[0016] As a further technical solution, the boiling time is 60 to 90 minutes.

[0017] As a further technical solution, the concentration of sodium bicarbonate in the sodium bicarbonate aqueous solution is 0.05wt%~0.1wt%.

[0018] As a further technical solution, the concentration of the carboxymethyl chitosan in the carboxymethyl chitosan aqueous solution is 3wt%~6wt%.

[0019] As a further technical solution, the mass ratio of the carboxymethyl chitosan aqueous solution to the silk nanofiber hydrogel is 2:1-4.

[0020] As a further technical solution, the silk dissolving solution in S1 is a lithium bromide solution.

[0021] As a further technical solution, the solute in the lithium bromide solution is lithium bromide, and the concentration of lithium bromide in the lithium bromide solution is 10 mol / L.

[0022] As a further technical solution, the mass ratio of the degummed silk to the lithium bromide in the lithium bromide solution is 1:0.5.

[0023] As a further technical solution, the solvent in the lithium bromide solution is water.

[0024] As a further technical solution, the preparation method of the silk nanofiber hydrogel includes the following steps: adding the degummed silk into the lithium bromide solution and mixing evenly, after hydrolysis, removing the lithium bromide by dialysis process, centrifuging, collecting the supernatant, and obtaining the silk nanofiber hydrogel.

[0025] As a further technical solution, the hydrolysis temperature is 35° C. and the hydrolysis time is 5 hours.

[0026] As a further technical solution, the centrifugal speed is 3000-10000 rpm, and the centrifugal time is 5-10 min.

[0027] As a further technical solution, the concentration of silk nanofibers in the silk nanofiber hydrogel in S1 is 0.5wt%~2wt%.

[0028] The present invention also provides the use of the composite dressing for long-term promotion of skin wound healing or the composite dressing prepared by the preparation method of the composite dressing for long-term promotion of skin wound healing in promoting skin wound healing.

[0029] The working principle and beneficial effects of the present invention are: The present invention proposes a novel composite dressing, which is composed of carboxymethyl chitosan, nano silk fiber and forskolin. The composite dressing can not only provide physical protection and a moist environment, but also promote angiogenesis by controlled release of forskolin, thereby accelerating the healing process of the wound surface. Moreover, since the composite dressing of the present invention has a slow release effect, the composite dressing can also promote the healing of skin wounds in a long term, solving the problems of low drug delivery efficiency and single function of wound dressings. Forskolin is an active ingredient of the composite dressing. Compared with commonly used active ingredients such as growth factors, the composite dressing containing forskolin can better promote angiogenesis and accelerate the healing process of the wound surface. In addition, the preparation method of the dressing is simple, cost-effective, and has good clinical application prospects. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] The present invention will be further described in detail below in conjunction with the accompanying drawings and specific embodiments.

[0031] Figure 1 This is a graph showing the results of a slow-release effect test of the present invention; Figure 2 This is a graph showing the test results of determining the concentration of Forskolin according to the present invention; In the figure: A is a live / dead staining test of vascular endothelial cells, B is a cell activity measurement result of vascular endothelial cells, C is a live / dead staining test of mouse fibroblasts, and D is a cell activity measurement result of mouse fibroblasts; Figure 3 Experimental diagram to promote skin wound healing; In the figure: A is a diagram illustrating wound formation and the experimental process in chronological order. B is a representative image of the progress of wound closure on days 0, 3, 7, and 14 after wound formation and intervention. C is a quantitative assessment of the remaining wound area at predetermined time intervals. D. Wound closure rate 14 days after surgery; Figure 4 This is the result of HE staining; Figure 5 This is a picture showing the staining to observe collagen deposition; In the figure: A is the Masson staining to observe collagen deposition on the 7th and 14th day after wound formation, and B is the immunohistochemical staining of α-SMA, Collagen-I, CD31 and CD34 on the 7th day after surgery. DETAILED DESCRIPTION

[0032] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0033] In the following examples and comparative examples: Forskolin: Purity 98.71%.

[0034] Example 1 A method for preparing a composite dressing for promoting skin wound healing in a long-term manner comprises the following steps: S1, degumming natural mulberry silk with 0.05wt% sodium bicarbonate aqueous solution for 60min, washing with water, and drying to obtain degummed mulberry silk; S2, adding the degummed mulberry silk to a 10 mol / L lithium bromide aqueous solution, mixing evenly, and hydrolyzing at 35°C for 5 hours to obtain a hydrolysis mixture; wherein the mass ratio of the degummed mulberry silk to the lithium bromide in the lithium bromide aqueous solution is 1:0.5; S3, dialyzing the hydrolysis mixture in a dialysis bag containing water, removing lithium bromide, centrifuging at 3000 rpm for 10 minutes, and collecting the supernatant, which is the mulberry silk nanofiber hydrogel; wherein the concentration of degummed mulberry silk in the mulberry silk nanofiber hydrogel is 2wt%; S4, mixing 3 wt % of carboxymethyl chitosan aqueous solution and mulberry silk nano-hydrogel in a mass ratio of 1:1 and stirring for 10 min to obtain a mixed gel; S5. Evenly mix forskolin and the mixed gel to prepare a composite dressing; the concentration of forskolin in the composite dressing is 10 μM.

[0035] Example 2 A method for preparing a composite dressing for promoting skin wound healing in a long-term manner comprises the following steps: S1, degumming natural mulberry silk with 0.08wt% sodium bicarbonate aqueous solution for 80min, washing with water, and drying to obtain degummed mulberry silk; S2, adding the degummed mulberry silk to a 10 mol / L lithium bromide aqueous solution, mixing evenly, and hydrolyzing at 35° C. for 5 h to obtain a hydrolysis mixture; wherein the mass ratio of the degummed mulberry silk to the lithium bromide in the lithium bromide aqueous solution is 1:0.5; S3, placing the hydrolysis mixture in a dialysis bag containing water for dialysis, removing lithium bromide, centrifuging at a speed of 5000 rpm for 8 minutes, and collecting the supernatant, which is the mulberry silk nanofiber hydrogel; wherein the concentration of degummed mulberry silk in the mulberry silk nanofiber hydrogel is 0.5wt%; S4, mixing 5 wt% of carboxymethyl chitosan aqueous solution and mulberry silk nanofiber hydrogel in a mass ratio of 2:1 and stirring for 10 min to obtain a mixed gel; S5. Mix forskolin and the mixed gel evenly to prepare a composite dressing; the concentration of forskolin in the composite dressing is 8 μM.

[0036] Example 3 A method for preparing a composite dressing for promoting skin wound healing in a long-term manner comprises the following steps: S1, degumming natural mulberry silk with 0.1wt% sodium bicarbonate aqueous solution for 90min, washing with water, and drying to obtain degummed mulberry silk; S2, adding the degummed mulberry silk to a 10 mol / L lithium bromide aqueous solution, mixing evenly, and hydrolyzing at 35° C. for 5 h to obtain a hydrolysis mixture; wherein the mass ratio of the degummed mulberry silk to the lithium bromide in the lithium bromide aqueous solution is 1:0.5; S3, placing the hydrolysis mixture in a dialysis bag containing water for dialysis, removing lithium bromide, centrifuging at a speed of 10000 rpm for 5 minutes, and collecting the supernatant, which is the mulberry silk nanofiber hydrogel; wherein the concentration of degummed mulberry silk in the mulberry silk nanofiber hydrogel is 1wt%; S4, mixing 6 wt % of carboxymethyl chitosan aqueous solution and mulberry silk nanofiber hydrogel in a mass ratio of 1:2 and stirring for 10 min to obtain a mixed gel; S5. Evenly mix forskolin and the mixed gel to prepare a composite dressing; the concentration of forskolin in the composite dressing is 12 μM.

[0037] Comparative Example 1 Compared with Example 1, the only difference of this comparative example is that the silk nanofiber hydrogel is replaced with an equal amount of water to prepare a composite dressing.

[0038] Test Example 1 Slow Release Effect Test A mixed gel with a forskolin concentration of 100 μM was prepared according to the methods in Example 1 and Comparative Example 1, and a slow release effect test was performed. The test method is as follows: 1 mL of the mixed dressing was added to an equal volume of PBS buffer (pH 7.4), mixed evenly, and allowed to stand. After a predetermined standing time (1d, 3d, 5d, 7d, 14d), the composite dressing was centrifuged at a rate of 1000 r / min for 5 min, 1 mL of the supernatant was removed, and then supplemented with an equal volume of PBS buffer and mixed evenly. The content of Forskolin in the supernatant was determined by high performance liquid chromatography, the release curve of Forskolin was calculated, and the percentage of Forskolin released at different times was calculated. The composite dressing in Example 1 was recorded as CCSF-FSK, and the composite dressing in Comparative Example 1 was recorded as CC-FSK. The test results are shown in FIG. Figure 1 shown.

[0039] pass Figure 1 The results show that it can be analyzed that: forskolin is slowly and continuously released in CCSF-FSK until it reaches the peak release in about 7 days; while forskolin reaches the peak release in about 1 day in CC-FSK when CC-FSK is used alone. Therefore, the composite dressing prepared in Example 1 of the present invention has a slow release effect.

[0040] Experimental Example 2 Determination of Forskolin Concentration A1. Cells were seeded in 96-well plates (1×10 4 cells / well) and cultured in H-DMEM medium at 37°C in a 5% CO2 cell culture incubator overnight; the cells used in the experiment included vascular endothelial cells and mouse fibroblasts.

[0041] A2. Different concentrations of Forskolin (i.e., 0μM, 5μM, 10μM, and 15μM) were added to the cell culture medium and incubated for 24h, 48h, 72h, and 96d, respectively. The control group was replaced with fresh DMEM culture medium, and live / dead staining test and cell viability assay were performed, respectively. The control group was recorded as Control; 0μM Forskolin, 5μM Forskolin, 10μM Forskolin, and 15μM Forskolin groups were recorded as SNF, SNF-FSK5, SNF-FSK10, and SNF-FSK15, respectively.

[0042] A3. Live / dead staining assay (Calcein-AM / PI assay): cells were seeded in 12-well plates (1×10 5 The cell culture medium was replaced with different concentrations of Forskolin (i.e., 0 μM, 5 μM, 10 μM, and 15 μM) in 4 wells (cells / well) and incubated for 24 h. Calcein-AM (10 μg / mL) and propidium iodide PI (10 μg / mL) were used for darkroom staining. After incubation for 30 min, images were taken using a fluorescence microscope (Olympus, Japan). The measurement results are shown in Figure 2. Figure 2 As shown in A (vascular endothelial cells) and C (mouse fibroblasts).

[0043] The experimental results showed that the cells in the SNF group and SNF-FSK group with low concentrations of Forskolin (5μM and 10μM) were stained green and a small amount of red, while the proportion of cells stained red increased in the high concentration Forskolin group (15μM). Compared with the control, when the concentration of forskolin in the composite dressing was 5-10μM, it had no substantial effect on cell viability, and the number of living cells in vascular endothelial cells and mouse fibroblasts was the largest when the concentration of Forskolin was 10μM (green stained cells were living cells, and red stained cells were dead cells).

[0044] A4. Cell viability assay: Determine the cell viability at a Forskolin concentration of 10 μM; The cells in A2 were incubated for 24 h, 48 h, 72 h, and 96 d in the SNF-FSK10 group, SNF group, and Control group, respectively. After incubation with CCK-8 reagent (10 μL / well) for 1 h, the OD value at a wavelength of 450 nm was measured using a microplate reader. The OD value directly reflects the cell viability.

[0045] The results showed that compared with the control group, there was no significant change in cell viability when SNF was used alone, indicating that SNF had no significant cytotoxicity. Figure 2As shown in B (vascular endothelial cells) and D (mouse fibroblasts), the results show that the composite dressing containing 10 μM concentration of Forskolin promotes the proliferation of HUVEC cells (B) and mouse fibroblasts (D) at 24h, 48h, 72h, and 96d.

[0046] Test Example 3 Test on promoting collagen deposition and wound healing Animal experiments were conducted with the approval of the Theoretical Committee of the PLA General Hospital. The specific experimental methods are as follows B1. Nine C57 BL / c male mice weighing 18-22 g were purchased and anesthetized with intraperitoneal injection of sodium pentobarbital. A full-thickness defect with a diameter of 7 mm × 7 mm was made using a trephine. B2. The animals were randomly divided into 3 groups: untreated group, CCSF hydrogel group (composite dressing was the composite dressing without forskolin in Example 1) and CCSF-FSK group (composite dressing was the composite dressing in Example 1), and each group was treated with 150 mL of the dressing immediately after the wound was formed. The mice were killed on the 7th, 14th and 21st day, and the skin tissues were taken after taking photos; B3. Fix the excised skin tissue specimens in 10% neutral formalin buffer overnight and then store them in 70% ethanol; B4. The fixed tissues were dehydrated through an ethanol series and embedded in paraffin, and each tissue block was cut into several 5-µm sections using a tissue processor for histological examination; B5, morphological observation was performed using a hematoxylin-eosin (HE) staining kit; B6, Masson staining using Masson staining kit; B7. Immunohistochemical staining was used to detect the expression of vascular-related markers CD31 and CD34 and collagen deposition-related α-SMA and Collagen-I in skin tissue. The specific process is as follows: the cut tissue sections were treated with 0.3% H2O2 for 15 minutes, and then treated with blocking solution for 1 hour. Anti-α-SMA antibody and anti-Collagen-Ⅰ antibody were incubated and kept at 4°C overnight. The sections were then rinsed, incubated with secondary antibodies at 37°C for 30 minutes, DAB reaction was performed, and hematoxylin was stained again, and the sections were sealed with paraffin oil for storage in preparation for photography; B8. Use Image J software to measure the wound area on the 7th and 14th days, and calculate the expression of α-SMA and Collagen-Ⅰ to determine the amount of collagen deposition. The test results are as follows: Figures 3-5 shown.

[0047] Figure 3In the experiment, CCSF-FSK hydrogel promoted wound healing after being applied to the skin wound. A. Schematic diagram of wound formation and experimental process in chronological order. B. Representative images of wound closure progress on days 0, 3, 7, and 14 after wound formation and intervention. C. Quantitative assessment of the remaining wound area at predetermined time intervals. D. Wound closure rate 14 days after surgery.

[0048] Figure 4 In the figure, HE staining results after CCSF-FSK hydrogel treatment. The black arrows indicate new blood vessels, and the blue arrows indicate new hair follicles.

[0049] Figure 5 A. Masson staining on the 7th and 14th days after wound formation to observe collagen deposition (the more blue is displayed, the richer the collagen deposition). B. Immunohistochemical staining of α-SMA, Collagen-I, CD31 and CD34 on the 7th day after surgery. Brown-stained cells are positively expressed cells (the positive expression of α-SMA and Collagen-I represents the amount of collagen deposition, and the more CD31 and CD34 expression represents the more neovascularization.

[0050] By analyzing Figure 3 It can be seen that the wound healing speed of the CCSF-FSK treatment group was significantly faster than that of the other research groups. The wound healing rate of the CCSF-FSK group was about 40.17% on the third day after surgery, and the wound healing rate increased to 78.78% on the 7th day after surgery, while the wound healing rates of the blank control group and CCSF group on the 7th day after surgery were only 53.45% and 62.74%. The results showed that the wound healing and functional recovery of the CCSF-FSK group were better than those of the untreated control group and CCSF treatment group.

[0051] By analyzing Figure 4 It can be seen that the wounds treated with CCSF-FSK healed faster, had higher blood vessel density and fewer inflammatory cells. New hair follicles appeared in the CCSF-FSK-treated group on the 21st day, indicating that CCSF-FSK can promote hair follicle regeneration.

[0052] By analyzing Figure 5It can be seen that the CCSF-FSK group has increased collagen deposition compared with the other groups, which is mainly reflected in the higher expression levels of α-SMA and Collagen-I. In order to comprehensively evaluate the characteristics of the dressing, the present invention intends to evaluate the number of new blood vessels during wound healing. CD31 and CD34 are markers of endothelial progenitor cells, representing endothelial cells of mature and immature blood vessels, respectively. Therefore, the present invention uses immunohistochemistry to detect the expression of CD31 and CD34 on the 7th day after injury, which is the critical period of neovascularization. Compared with the other treatment groups, the expression of CD31 and CD34 in the CCSF-FSK group was significantly increased, indicating that the density of new blood vessels in the wound bed increased.

[0053] Therefore, the composite dressing of the present invention can accelerate wound repair by stimulating angiogenesis.

[0054] The above are only preferred embodiments of the present invention and are not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A composite dressing for promoting skin wound healing in a long-term manner, characterized in that: The raw materials of the composite auxiliary material include: carboxymethyl chitosan, silk nanofiber hydrogel and forskolin.

2. The composite dressing for promoting skin wound healing in a long term according to claim 1, characterized in that: The concentration of forskolin in the composite dressing is 5-15 μM.

3. A method for preparing a composite dressing for promoting skin wound healing in a long term according to any one of claims 1 to 2, characterized in that: The following steps are involved: S1, adding degummed silk into silk dissolving solution and mixing evenly to obtain silk nanofiber hydrogel; S2, mixing the carboxymethyl chitosan aqueous solution and the silk nanofiber hydrogel evenly to obtain a mixed gel; S3. Evenly mix the forskolin and the mixed gel to prepare a composite dressing.

4. The method for preparing a composite dressing for promoting skin wound healing in a long term according to claim 3, characterized in that: The degummed silk is obtained by degumming silk with a sodium bicarbonate solution.

5. The method for preparing a composite dressing for promoting skin wound healing in a long term according to claim 3, characterized in that: The concentration of the carboxymethyl chitosan in the carboxymethyl chitosan aqueous solution is 3wt%-6wt%.

6. The method for preparing a composite dressing for promoting skin wound healing in a long term according to claim 3, characterized in that: The mass ratio of the carboxymethyl chitosan aqueous solution to the silk nanofiber hydrogel is 2:1-4.

7. The method for preparing a composite dressing for promoting skin wound healing in a long term according to claim 3, characterized in that: The silk dissolving solution in S1 is a lithium bromide solution.

8. The method for preparing a composite dressing for promoting skin wound healing in a long term according to claim 7, characterized in that: The solute in the lithium bromide solution is lithium bromide, and the concentration of lithium bromide in the lithium bromide solution is 10-15 mol / L.

9. The method for preparing a composite dressing for promoting skin wound healing in a long term according to claim 3, characterized in that: The concentration of silk nanofibers in the silk nanofiber hydrogel in S1 is 0.5wt%~2wt%.

10. Use of a composite dressing prepared according to the method for preparing a composite dressing for long-term promotion of skin wound healing according to any one of claims 1 to 2 or any one of claims 3 to 9 in promoting skin wound healing.